2004
DOI: 10.1007/s10147-004-0430-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of carcinogenesis in familial tumors

Abstract: It is thought that malignant tumors occur through interactions of multiple environmental factors and a personal genetic factor. A normal somatic cell having an intrinsic function is able to acquire the characteristics of a malignant cell under the influence of many factors. A small percentage of all tumors have obvious familial aggregation. These entities are called familial cancer. The familial cancer syndrome is well defined for colorectal cancer, breast cancer, endocrine neoplasia, and so on. Traits of fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 27 publications
0
7
1
Order By: Relevance
“…Stability genes may also be affected, such as those involved in Fanconi's anemia. 5 Patients with these syndromes frequently present concomitant neoplasms at specific sites, mostly at a younger age, with features differing from those of the seven cases reported in this study.…”
Section: Discussioncontrasting
confidence: 72%
“…Stability genes may also be affected, such as those involved in Fanconi's anemia. 5 Patients with these syndromes frequently present concomitant neoplasms at specific sites, mostly at a younger age, with features differing from those of the seven cases reported in this study.…”
Section: Discussioncontrasting
confidence: 72%
“…Colorectal cancer (CRC) is one of the most prevalent malignancies throughout the world and the third leading cause of cancer death in Japan. Therefore, elucidation of its etiology and development of therapeutic measures are very important (1). To date, a number of studies of CRC development have shown that the etiology is very complex, because of complicated interactions among various environmental factors and a large number of genetic alterations.…”
Section: Introductionmentioning
confidence: 99%
“…Its amplification is an event that occurs in primary OS (3-25%) and it is overexpressed in metastases and recurrences [31,32]. CHEK2 is another protein that is part of a DNA damage checkpoint, works as a stabilizer of TP53, and shows a 7% frequency of mutations in OS patients [33,34].…”
Section: Discussionmentioning
confidence: 99%